A Tree-Based Distributed Permutation Routing Protocol in Multi-Hop Wireless Sensors Network - Bomgni, Alain B.; Fute, Elie T.; Sindjoung, Miguel L. F.; Djamegni, Clémentin T. (Scientific Research Publishing, 2016)
A Wireless Sensors Network (WSN) is an ad-hoc network populated by small hand-held commodity devices, running on batteries called stations or sensors. Often used in hostiles and sometimes unreachable environments, stations are subject to energetic constraints which can significantly decrease the network life time. Permutation routing problem is mainly found in the literature of WSN. This problem occurs when some stations have items that belong either or not to them. The goal is to send each item to its receiver. To solve this problem, several works are presented in the literature. In this paper, we present a new permutation routing protocol for multi-hop wireless sensors network that, compared to recent work in the field is more efficient in terms of conservation of sensors’ energy, which results in a longer life time of the network. Also, contrary to some other routing protocols which assume that the memory of the sensors is infinite, we show that the memory size of the sensors is limited, which in our opinion is more realistic.
Keywords: Clique; Cyclic Reception; Hierarchical Clustering; Permutation Routing Problem; Wireless Sensors Network